PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 80 BUMBUNG - Fitriyanti Fitriyanti; Zuhri D Zuhri D; Japet Ginting (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study is motivated by the results of the study of mathematics students classified as very low, from 28 students only 13 students who achieved more than or equal to 70 in KKM or only 46.4%. This study aims to improve the learning outcomes of students with mathematics learning TPS model in the fourth grade at SDN 80 Bumbung. The type of the research is Classroom Action Research, which conducted in two cycles with using the observation sheet of teachers and students activities and daily tests, which analyzed by descriptive qualitative, while the daily tests will be analyzed with analysis of mastery learning math, and a frequency distribution analysis. The results of this research showed an increase in students' mathematics learning outcomes from above KKM on the basic score there were 13 students (46.4%), the first daily test increased to 19 students (67.9%), and the daily tests II increased again to 23 students (82.1%). It conclude that the application of the teaching TPS model in fourth grade SDN 80 Bumbung can improve the process of learning and improve the students' mathematics learning outcomes. Key words : Models of Learning Think Pair Square (TPS), the learning process, learning math results.